Extending Absorption of Cs2AgBiBr6 to Near‐Infrared Region (≈1350 nm) with Intermediate Band. (10th December 2021) - Liu, Ganghong; Zhang, Zehao; Wu, Cuncun; Zhang, Yuqing; Li, Xiangdong; Yu, Wenjin; Yao, Guangjie; Liu, Shiming; Shi, Jun‐jie; Liu, Kaihui; Chen, Zhijian; Xiao, Lixin; et al.
Abstract: The toxicity of lead‐based halide perovskites hampers broad application in optoelectronics. Lead‐free perovskite Cs2 AgBiBr6 is considered a promising candidate, owing to the long carrier lifetime and great stability. However, the relatively large bandgap of 1.98 eV limits its absorption in the visible region. Herein, Fe 2+ is chosen as the dopant to alloy into Cs2 AgBiBr6 single crystals, and results in an absorption range broadening to ≈1350 nm, which is the longest near‐infrared (NIR) response recorded among lead‐free perovskites. About 1% of Fe ions are alloyed into the Cs2 AgBiBr6 lattice to cause lattice shrink age. Instead of narrowing the bandgap, Fe doping would introduce a new intermediate band inside the pristine bandgap of Cs2 AgBiBr6 to strongly absorb NIR light, as confirmed by third harmonic generation results. Moreover, considerable photogenerated carriers are produced in Fe doped Cs2 AgBiBr6 crystals with NIR irradiation. This work has provided a new way to extend the optical response of lead‐free perovskites for NIR photodetectors and intermediate band photovoltaics. Abstract : Fe is alloyed into Cs2 AgBiBr6, extending the absorption edge to the near infrared (NIR) region (≈1350 nm), which is the longest absorption for lead‐free perovskite. A new intermediate band, contributing to the NIR absorption, is observed, indicating a new way to extend the optical response for lead‐free perovskite to NIR photodetectors and intermediate band photovoltaics.